Developing a Field of Study in Implementation Science for the Africa Region: The Wits–UNC AIDS Implementation Science Fogarty D43. (March 2020) - Ramaswamy, Rohit; Chirwa, Tobias; Salisbury, Kathryn; Ncayiyana, Jabulani; Ibisomi, Latifat; Rispel, Laetitia; van der Horst, Charles; Pettifor, Audrey
From 2014 to 2019, the Wits–UNC (University of Witwatersrand and University of North Carolina at Chapel Hill) AIDS Implementation Science D43 Training Program laid critical academic foundation by creating a graduate degree program in implementation science (IS) for master's- and doctoral-level students in the Department of Epidemiology and Biostatistics at the Wits School of Public Health. Before this collaboration, funded by the Fogarty International Center (FIC) at National Institutes of Health, no IS degree existed in Southern Africa. The FIC "D43" is an international research training grant mechanism to strengthen global health research expertise through education. Historically, students from low-resource settings have been trained in health sciences at universities in the United States or the United Kingdom. This is not scalable or sustainable and therefore this D43 focused on building capacity in South Africa where HIV-related challenges are located. Consequently, South Africans and other African international students were able to apply to the newly offered program, allowing training at significantly lower costs. IS allows a systematic assessment of factors affecting the implementation of HIV interventions and in developing strategies for addressing them. It guides the successful scale-up of effective programs and informs policy to improve programs. The training aims to assist in lowering the HIV incidence rate, suppressing viral load for those infected, and meeting the UN 2030 Agenda for Sustainable Development. A second cycle of funding from 2019 to 2024 will enable the infrastructure built in the first program to train South African HIV researchers and practitioners in the field who are unable to enroll in a formal academic program.